The East Coast or the Death. Performing Expedition Tourism on the Greenlandic icecap - Moen, Cathrine (UiT The Arctic University of Norway, 2014)
In 1888 Fridtjof Nansen led the first crossing over Greenland, this was seen as a huge accomplishment and the expedition gain great recognition. Today more than 125 years later we see that people still follows in the historical “footsteps” of polar explorers. Often led by tourism companies who provide various ski expeditions in the polar regions, both in the Arctic and Antarctica. This thesis will explore the expedition phenomenon through Edensor’s perspective of performance within tourism. The study brings up reflections on the phenomenon that can function as a source to get more insight to the participant’s relation to the concept and how they ascribe meaning to the phenomenon while being on the move in the polar nature for a month. Expedition tourism can be a way to perform identity, on a ski expedition in a tourism context, identities related to gender-, friluftsliv- and national-identity seems relevant. Keywords: expedition tourism, performance, Edensor, Greenland, Nansen, meaning, identity, friluftsliv, cultural heritage